(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Delima-Baron EM, Ruales CAS, Tripole C. Tagoon MDT, Susulan TB. 2022. Anurans of select green spaces of Davao City, Mindanao Island, Philippines. Biodiversitas 23: 4810-4815. Data on anurans in green spaces, especially in highly urbanized cities, including Davao, is still very limited. We present for the first time a checklist of anuran species from six green spaces of Davao City previously not surveyed for anuran data. Anurans were documented from January to April 2019 using visual encounter techniques coupled with microhabitat searches on several nocturnal surveys. Eighteen species representing seven families were recorded. Three endemic species: Pelophryne brevipes, Fejervarya moodiei, and F. vittigera, were added to the current list of anurans known from green spaces of Davao City, bringing the total known species for Davao City to 23. Thirteen of the species recorded are endemic. Two species under the Near Threatened category of IUCN, Limnonectes magnus and Sanguirana everetti, were also documented. The study also accounted for four invasive species: Rhinella marina, Eleutherodactylus planirostris, Hoplobatrachus rugulosus, and Kaloula pulchra. However, these species were encountered only in sites with artificial structures nearby, prominent noise, and has less heterogeneous vegetation. Data adds to the limited account of anurans in Davao City’s green spaces. Adding more species also implies that the list of anurans from Davao City’s green spaces is far from complete. Exploration of other green spaces available in the city is necessary to fully understand anuran species composition and the value of green spaces to the persistence of this taxon even in highly urbanized areas.